2019
DOI: 10.3390/insects10010023
|View full text |Cite
|
Sign up to set email alerts
|

Consumption Rate of Lichens by Constrictotermes cyphergaster (Isoptera): Effects of C, N, and P Contents and Ratios

Abstract: Wood is the main dietary item for most termites; however, supplementation with certain nutrients may occur via the ingestion of other available food resources in the ecosystem. The objective of this study was to evaluate the consumption of lichens with different C, N, and P contents by Constrictotermes cyphergaster under laboratory conditions, and estimate the intake of this substrate by this species in a semi-arid area of Northeast Brazil. The foraging activities of fifteen field colonies were monitored over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…Termites are detritivores feeding mainly on plant‐based materials including dead wood, leaf litter, grasses and soil varying in organic matter content (Donovan, Eggleton & Bignell, 2001). Less typical food includes epiphytic lichens, mammalian dung and vertebrate carcasses (Eggleton & Tayasu, 2001; Prestes et al ., 2014; Barbosa‐Silva & Vasconcellos, 2019). Phylogenetically basal termites, ‘lower termites’, such as Rhinotermitidae and Kalotermitidae, feed on dead wood or grass as a primary food source, and digest it with the help of symbiotic protists in their gut.…”
Section: Synopsis Of Feeding Habitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Termites are detritivores feeding mainly on plant‐based materials including dead wood, leaf litter, grasses and soil varying in organic matter content (Donovan, Eggleton & Bignell, 2001). Less typical food includes epiphytic lichens, mammalian dung and vertebrate carcasses (Eggleton & Tayasu, 2001; Prestes et al ., 2014; Barbosa‐Silva & Vasconcellos, 2019). Phylogenetically basal termites, ‘lower termites’, such as Rhinotermitidae and Kalotermitidae, feed on dead wood or grass as a primary food source, and digest it with the help of symbiotic protists in their gut.…”
Section: Synopsis Of Feeding Habitsmentioning
confidence: 99%
“…Soil communities comprise prokaryotes and fungi, which release enzymes into the environment for food digestion, and heterotrophic protists and animals (hereafter termed 'consumers' for simplicity), which ingest food resources from the environment and digest them inside their body. Together, they form the decomposer system responsible for fundamental ecosystem functions such as decomposition of organic matter, nutrient release, soil aggregation and plant growth, and supporting aboveground food webs (Lavelle, 1996;Bardgett, Hopkins & Usher, 2005;Wagg et al, 2014;Steffan & Dharampal, 2018). Soils host about 50% of global animal biomass (Fierer et al, 2009) and the majority of terrestrial animal biodiversity is associated with soil and litter as a habitat or food source (Table 1).…”
Section: Introduction (1) Belowground Consumers and Ecosystem Functio...mentioning
confidence: 99%
“…We understand the importance of research with controlled variables, such as temperature and moisture, but nonetheless encourage more field observations that can be merged with laboratory observations. Studies carried out in the Cerrado areas demonstrated fewer field experiments than those carried out in the Caatinga domain, resulting in gaps in our knowledge in the Cerrado areas concerning interactions with termitophiles during foraging ( Figure 6 ) [ 40 , 41 ], lichen consumption ( Figure 7 ), the identification of the assemblage composition of the lichens consumed, and the possible relationships between lichens and nests [ 21 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lichen consumption is also a fertile research subject, as little is currently known about many aspects of this rather rare behavior among termites, with significant gaps in our knowledge of the behavior and the nutritional ecology of this species [ 23 , 38 , 42 , 44 ] that deserve investigation. (1) If lichens are important dietary items of this species [ 42 ], how does C. cyphergaster behave when deprived of that resource? Do they search for alternative dietary complements?…”
Section: Discussionmentioning
confidence: 99%
“…The only exception was observed in soldier caste of M. subhyalinus exposed to mixture of N. tabacum and J. curcas, where 92% mortality was recorded within 6-h exposure. The soldier termites are usually less mobile than the worker termite since they are less involved in the collection of cellulose for the colony unlike the worker termites (Barbosa-Silva & Vasconcellos, 2019;Watanabe, Gotoh, Miura, & Maekawa, 2014). The characteristic lower mobility of the soldier termite on wet treated filter paper could have reduced their ability to pick up more plant extracts unlike worker termites and this could be responsible for the observed lower mortality in soldier termite.…”
Section: Discussionmentioning
confidence: 99%